2019
DOI: 10.1111/pan.13601
|View full text |Cite
|
Sign up to set email alerts
|

Serious airway‐related adverse events with sevoflurane anesthesia via facemask for magnetic resonance imaging in 7129 pediatric patients: A retrospective study

Abstract: Summary Objective This retrospective study evaluated the safety and effectiveness of sevoflurane anesthesia by facemask for magnetic resonance imaging (MRI) scanning among pediatric patients in a high‐volume MRI department. Methods The medical records of 7129 pediatric patients (median age 12 months, range 4.0‐36.0 months) who were administered anesthesia during MRI scanning were reviewed. Anesthesia via 8% and 1.5%‐2% sevoflurane was used for induction and maintenance, respectively. All the patients were moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Sevoflurane anesthesia provides higher success rates (92% vs. 80%) and faster onset and recovery, but a higher incidence of emergence delirium than propofol anesthesia in children undergoing MRI [70,76]. Major airway-related adverse events such as respiratory apnea and severe airway obstruction occurred in 0.4% of children, while preterm infants are at higher risk compared to term infants after sevoflurane anesthesia for MRI [81]. Positive pressure ventilation with endotracheal intubation or LMA may result in more extensive atelectasis in children after MRI compared to spontaneous ventilation in children receiving sevoflurane-based anesthesia [78,82].…”
Section: ) Propofolmentioning
confidence: 99%
“…Sevoflurane anesthesia provides higher success rates (92% vs. 80%) and faster onset and recovery, but a higher incidence of emergence delirium than propofol anesthesia in children undergoing MRI [70,76]. Major airway-related adverse events such as respiratory apnea and severe airway obstruction occurred in 0.4% of children, while preterm infants are at higher risk compared to term infants after sevoflurane anesthesia for MRI [81]. Positive pressure ventilation with endotracheal intubation or LMA may result in more extensive atelectasis in children after MRI compared to spontaneous ventilation in children receiving sevoflurane-based anesthesia [78,82].…”
Section: ) Propofolmentioning
confidence: 99%
“…However, our previous clinical observation found that airway adverse events such as holding breath and coughing were easy to occur during the resuscitation of sevoflurane anesthesia in children (Li J, et al, 2013). Similarly, a recent study also reported that the incidence of adverse airway events in premature infants under sevoflurane anesthesia was higher than that in normal infants, which may be related to airway immaturity (Lei H, et al, 2019). The above studies suggest that in special conditions, such as very low concentrations of sevoflurane are not sufficient to produce protective effects or airway is immature, the nociceptive effect may return to the dominant role, resulting in a series of airway adverse events.…”
Section: Discussionmentioning
confidence: 90%
“…Our results show a higher incidence of total anesthesia-related AEs than previously described in literature for pediatric procedural sedation or anesthesia. 36 Most of the reports are based on retrospective data analysis 37,38 or voluntary self-reporting 39,40 and focus on serious AEs requiring immediate interventions. 36,40 These aspects might lead to underestimation of total AEs.…”
Section: Discussionmentioning
confidence: 99%